Two New Lessons from Asian Miracles - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 2007)
Four Asian economies – Hong Kong, Singapore, Korea and Taiwan – have grown at spectacular speeds adopting different strategies. Past debates focused on their growth takeoff. The present paper studies their future outlook. As an economy matures, sustaining economic performance requires innovation and technology upgrading. Hong Kong, under a minimalist administration, is now critically deficient in technology. Singapore, dependent on foreign multinationals, is struggling to become a creator and not just a user of technology. We seek to explain why Hong Kong and Singapore are so much less innovative than Korea and Taiwan.